SEASONAL PATTERN OF PHYSIOLOGICAL STATE IN A CORK OAK (QUERCUS SUBER L.) STAND IN HUELVA (SPAIN) - GONZÁLEZ-PÉREZ, ARANTZAZU; VÁZQUEZ-PIQUÉ, JAVIER; TAPIAS, RAÚL; FERNÁNDEZ, MANUEL (Suberwood2005: New challenges for integration of cork oak forests and products, Scientific and Technical Conference, Huelva, Spain, 20, 21 and 22 October 2005., 2005)
The seasonal pattern of the physiological state of Quercus suber is determined by different ecological factors, and it affects to the growth of the species. The main objective of this study is to know the seasonal pattern of water potential, photosynthesis and fluorescence in four Quercus suber L. trees and to relate these values with ecological factors during two years. In this time there were three critical periods, the first one the end of the dry period where the water potential descends to values less than -3MPa and the photosynthesis to 0.781 µmol CO2m-2 s-1Quercus suber, physiology, water potential, photosynthesis, fluorescence. . The second critical period is located in period of change of the leaf, between the months of March and May. The third critical period occurred due to the freezes and drought of the year 2005, that produced strong damages in the PSII.
Keywords: fluorescenc; photosynthesis; physiology; Quercus suber; water potential

SEASONAL PATTERN OF PHYSIOLOGICAL STATE IN A CORK OAK (QUERCUS SUBER L.) STAND IN HUELVA (SPAIN) - GONZÁLEZ-PÉREZ, ARANTZAZU; VÁZQUEZ-PIQUÉ, JAVIER; TAPIAS, RAÚL; FERNÁNDEZ, MANUEL (Suberwood2005: New challenges for integration of cork oak forests and products, Scientific and Technical Conference, Huelva, Spain, 20, 21 and 22 October 2005., 2005)
The seasonal pattern of the physiological state of Quercus suber is determined by different ecological factors, and it affects to the growth of the species. The main objective of this study is to know the seasonal pattern of water potential, photosynthesis and fluorescence in four Quercus suber L. trees and to relate these values with ecological factors during two years. In this time there were three critical periods, the first one the end of the dry period where the water potential descends to values less than -3MPa and the photosynthesis to 0.781 µmol CO2m-2 s-1Quercus suber, physiology, water potential, photosynthesis, fluorescence. . The second critical period is located in period of change of the leaf, between the months of March and May. The third critical period occurred due to the freezes and drought of the year 2005, that produced strong damages in the PSII.
The following values have no corresponding Zotero field: periodical: Suberwood2005: New challenges for integration of cork oak forests and products, Scientific and Technical Conference, Huelva, Spain, 20, 21 and 22 October 2005. pub-location: Huelva
Keywords: fluorescenc; photosynthesis; physiology; Quercus suber; water potential